Effect analysis of the general complex reciprocal gyro-bianisotropic metamaterial medium on the input impedance of a printed dipole antenna - Mohamed Lamine Bouknia; Chemseddine Zebiri; Djamel Sayad; Issa Elfergani; Mohammad Matin; Arpan Desai; Jonathan Rodriguez; Tathababu Addepalli; Hasan Abobaker (Alexandria Engineering Journal, 2022)
The aim of this paper is to present an analytical study for the investigation of the reciprocal metamaterial gyro-bianisotropy effects on the input impedance of a dipole antenna. This study is based on the numerical resolution, using the spectral method of moments (SMoM), of the integral equation developed through the mathematical derivation of the appropriate spectral Green’s functions of the studied dipole configuration. The original obtained results are discussed and showed good agreements with the isotropic studied cases available in published literature. It is found that the imaginary valued magnetoelectric elements (chiral medium) exhibit an inverse effect on the resonant length compared to purely real elements (Tellegen medium), while negative elements decrease the input impedance. Combination of the two cases has led to more general complex media with further inspiring features.